Biotransformation of flubendazole and selected model xenobiotics in Haemonchus contortus - Cvilink, V; Kubícek, V; Nobilis, M; Krízová, V; Szotáková, B; Lamka, J; Várady, M; Kubenová, M; Novotná, R; Gavelová, M; Skálová, L (Veterinary parasitology, 2008)
Haemonchus contortus is one of the most pathogenic parasites of small ruminants (e.g., sheep and goat). The treatment of haemonchosis is complicated because of frequent resistance of H. contortus to common anthelmintics. The development of resistance can be facilitated by the action of drug metabolizing enzymes of parasites that can deactivate anthelmintics and thus protect parasites against the toxic effect of the drug. The aim of this project was to investigate the Phase I biotransformation of benzimidazole anthelmintic flubendazole in H. contortus and to determine the biotransformation of other model xenobiotics. For this purpose, in vitro (subcellular fractions of H. contortus homogenate) as well as ex vivo (live nematodes cultivated in flasks with medium) experiments were used. The results showed that cytosolic NADPH-dependent enzymes of H. contortus metabolize flubendazole via reduction of its carbonyl group. The apparent kinetic parameters of this reaction were determined (V'max=39.8+/-2.1 nM min(-1), K'm=1.5+/-0.3 microM). The reduction of flubendazole in H. contortus is stereospecific, the ratio of (-):(+) enantiomers of reduced flubendazole formed was 90:10. Reduced flubendazole was the only Phase I metabolite found. Effective reduction of other xenobiotics with carbonyl group (metyrapon, daunorubicin, and oracin) was also found. Significant activity of carbonyl-reducing enzymes may be important for H. contortus to survive the attacks of anthelmintics or other xenobiotics with carbonyl group.
Keywords: biotransformace; hemonchóza; oxidoreduktasy; Mebendazole; Sheep; Biotransformation; Animals; Sheep Diseases; Subcellular Fractions; subcelulární frakce; Oxidoreductases; mebendazol; Haemonchus; nemoci ovcí; zvířata; ovce; Haemonchiasis